Evidence of Power Practice between Teachers and Students: Insights from Classroom Discourse - Antonius Suratno; Heny Hartono (Soegijapranata Catholic University, 2025)
This study employs a conversation analysis, an approach rooted in ethnomethodology, to investigate how power dynamics are manifested in the speech patterns and interactional actions between teachers and students during English-language classroom discussions. The research, naturally qualitative, specifically examines two crucial conversational mechanisms: pauses, interruptions, and corrections to uncover the underlying social actions and power practices embedded within the turn-taking structure of these pedagogical interactions. By adopting an emic CA perspective, the study investigates two classroom conversations where two teachers were teaching speaking classes where fluency and accuracy are the pinnacle of the instructional goals. This study aims to gain insights into how the participants navigate and exercise power through the collaborative construction of meaning, which is central to the instructional objectives of the classroom discourse. The investigation of gaps and overlaps uncovered how both teachers and students exercise and navigate power dynamics through their verbal exchanges. The findings indicate that classroom discourse represents a multifaceted, collaborative process involving the dynamic interplay of power relations displaying non-conventional mode where students are empowered to express their participative roles. The observed gaps and overlaps in their turn-taking illustrate their cooperative efforts to construct meaning, reflecting their collective pursuit of instructional objectives